Analysis of the territorial thermal development of the Buenos Aires province Southwest applying the conflict methodology (Huellas, 2016)
In the process of globalization, it is observed that space, the notion of temporality and the different systems, -economic, socio-cultural, environmental and political- have suffered changes that affect in diverse ways the planetary reality. From the complex problems that affect reality as such, and as consequence of all the changes produced, permanent conflicts arise. The present work intends to understand the current processes that shape and re-shape the geographical space in the Southwest of the Buenos Airesprovince, from the perspective of the conflict methodology. Thus, we propose to examine the territorial thermal development in the Buenos Airesprovince Southwest with the purpose of analyzing the possible conflicts that could arise between the different actors involved in the constitution of the proposed tourist thermal route.
Keywords: globalization - geographical space - conflict methodology - thermal tourism of the Buenos Aires province southwest.